MOF‐Hosted Enzymes for Continuous Flow Catalysis in Aqueous and Organic Solvents. Issue 18 (9th March 2022) - Greifenstein, Raphael; Ballweg, Tim; Hashem, Tawheed; Gottwald, Eric; Achauer, David; Kirschhöfer, Frank; Nusser, Michael; Brenner‐Weiß, Gerald; Sedghamiz, Elaheh; Wenzel, Wolfgang; Mittmann, Esther; Rabe, Kersten S.; et al.
Abstract: Fully exploiting the potential of enzymes in cell‐free biocatalysis requires stabilization of the catalytically active proteins and their integration into efficient reactor systems. Although in recent years initial steps towards the immobilization of such biomolecules in metal–organic frameworks (MOFs) have been taken, these demonstrations have been limited to batch experiments and to aqueous conditions. Here we demonstrate a MOF‐based continuous flow enzyme reactor system, with high productivity and stability, which is also suitable for organic solvents. Under aqueous conditions, the stability of the enzyme was increased 30‐fold, and the space–time yield exceeded that obtained with other enzyme immobilization strategies by an order of magnitude. Importantly, the infiltration of the proteins into the MOF did not require additional functionalization, thus allowing for time‐ and cost‐efficient fabrication of the biocatalysts using label‐free enzymes. Abstract : A continuous flow enzyme reactor was developed using a metal–organic framework (MOF) to immobilize the enzyme. The MOF NU‐1000 was inserted into a HPLC column and loaded with esterase without any modification of the MOF or the enzyme. A high space‐time yield of 1432 g L −1  h −1 was achieved, and the stability of the immobilized enzyme was enhanced to about 30 times that of the free enzyme.